PENERAPAN GOOD MANUFACTURING PRACTICES (GMP) PADA PENGALENGAN RAJUNGAN (Portunus pelagicus) DI PT. SIGER JAYA ABADI, LAMPUNG - Herlambang, Denisha Azzahra; Wulandari, Wulandari; Afriani, Afriani; Hasanah, Hasanah; Yunita, Laura Hermala; Wulanda, Yoppie (Leuit (Journal of Local Food Security), 2024)
Crab (Portunus pelagicus) is one of the high-value export commodities butspoils quickly if not handled properly and quickly. Canning is one way ofpreserving crab. PT Siger Jaya Abadi is one of the crab canning companiesin Indonesia. In the canning process, the application of GMP will affect thequality of the products produced. The purpose of this study is to determinethe application of GMP (Good Manufacturing Practice) in the process ofcanning crab at Siger Jaya Abadi Inc. This research design is a descriptivemethod. The process of canning crab starting from the environment ofprocessing facilities is in a good place, clean, safe, and does not become asource of contaminants, buildings and physical facilities, buildings, floorswalls, roofs or ceilings, and windows or ventilation, in accordance withengineering and hygiene requirements, sanitation facilities have completefacilities, ranging from water, sanitation officers, toilets, machinery andequipment, The raw materials and additives used are in accordance withapplicable standards, and the production process starting from receiving rawmaterials, piking, sorting, weighing, mixing, filling, seaming, sealing, coding,pasteurizing, chilling, packing, up to export, is carried out in accordancewith the application of GMP. This shows that the crab canning process atSiger Jaya Abadi Inc. is in accordance with the assessment of the aspects ofGMP and has fulfilled the correct principles and procedures.